Correlation between Corneal Volume and Corneal Biomechanics and Corneal Volume Significance in Staging and Diagnosing Keratoconus - Zhiqing Wu; Yaohua Zhang; Yong Li; Fang Yang; Xirui Su; Yan Gao; Shengsheng Wei; Jing Li (Journal of Ophthalmology)
Purpose. To investigate the relationship between corneal volume (CV) at different zones and corneal biomechanics in keratoconus (KC) along with the significance of CV in diagnosing and staging KC. Methods. This prospective clinical study included 456 keratoconic eyes (Group B) and 198 normal eyes (Group A). Using the topographic KC classification method, Group B was divided into subgroups based on severity (mild, moderate, and severe). The CVs of the 3 mm, 5 mm, and 7 mm zones and biomechanical parameters were obtained by Pentacam and Corvis ST. The diagnostic utility of multirange CVs at different disease stages and severity was determined using a receiver operating characteristic (ROC) curve analysis. Results. The CV of the 7-mm zone had the strongest correlation with A1V, A2T, PD, DA ratio max (2 mm), DA ratio max (1 mm), ARTh, integrated radius, SPA1, and CBI p<0.01. The CVs of the Group B subgroups were significantly lower than those of Group A for each diameter range p<0.05. There were significant differences between the severe, mild, and moderate subgroups for the 3 mm zone (p<0.05, all). The 3 mm zone CV exhibited better diagnostic ability in each group for distinguishing KC from the normal cornea (Groups A vs. B: area under the ROC curve (AUC) = 0.926, Groups A vs. B1: AUC = 0.894, Groups A vs. B2: AUC = 0.925, Groups A vs. B3: AUC = 0.953). Conclusion. The CV significantly decreased in keratoconic eyes. Progressive thinning in the 3 mm zone may be a valuable measurement for detecting and staging KC. Combining the CV examination with corneal biomechanical information may effectively enhance the ability to detect KC.